Failed Attempts at Sino-Japanese Security Cooperation - Żakowski, Karol (Overcoming Controversies in East Asia, 2017)
The aim of this chapter is to analyze the reasons of failure in establishing a stable framework for Sino-Japanese security cooperation after the end of Cold War. Since the 1990s both countries have tried many times to strengthen mutual trust, institutionalize military exchange or create a telephone hotline for emergency situations, but so far these efforts have remained futile. While in 2006– 2010 it seemed that China and Japan started overcoming mutual prejudices, the situation deteriorated after the two East China Sea incidents in 2010 and 2012. The article argues that both countries have been unable to develop a full-fledged cooperation in the security field due to history problems, contrasting visions of regional security system, territorial disputes, and rivalry for leadership in East Asia. This article is a result of research conducted as a part of a project financed by the Polish National Science Centre based on decision No. DEC-2013/11/B/HS5/04005. In 2017 the author received the prize of the University of Lodz Foundation.